Ecotherapy as a form of supporting and stimulation to activity of the seniors - Kopczyński, Kazimierz (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The article presents a form of supporting and stimulation to activity of the seniors, little-known in geragogy and clinical gerontology, which is therapeutical influence of natural environment (ecotherapy). The use of ecotherapy in the induction of neurogenesis in the phase of old age is presented, as well as its use in creating the feeling of coherence, in supporting the seniors in critical situation, and also the meaning of ecotherapy for family life and strengthening family connections are emphasized. Here is an enormous potential in ecotherapy which can be functioning of the Universities of the Third Age or other institutions engaged in supporting and stimulation to activity of the seniors. used in many aspects of supporting the old. Ecotherapy should be very important factor in the functioning of the Universities of the Third Age or other institutions engaged in supporting and stimulation to activity of the seniors.